Pharmacological Activation of Autophagy Restores Cellular Homeostasis in Ultraviolet-(B)-Induced Skin Photodamage - Umar, Sheikh Ahmad; Shahid, Naikoo Hussain; Nazir, Lone Ahmad; Tanveer, Malik Ahmad; Divya, Gupta; Archoo, Sajida; Raghu, Sharma Rai; Tasduq, Sheikh Abdullah (Frontiers in Oncology, 2021)
Ultraviolet (UV) exposure to the skin causes photo-damage and acts as the primary etiological agent in photo-carcinogenesis. UV-B exposure induces cellular damage and is the major factor challenging skin homeostasis. Autophagy allows the fundamental adaptation of cells to metabolic and oxidative stress. Cellular dysfunction has been observed in aged tissues and in toxic insults to cells undergoing stress. Conversely, promising anti-aging strategies aimed at inhibiting the mTOR pathway have been found to significantly improve the ageing-related disorders. Recently, autophagy has been found to positively regulate skin homeostasis by enhancing DNA damage recognition. Here, we investigated the geno-protective roles of autophagy in UV-B exposed primary Human Dermal Fibroblasts (HDFs). We found that UV-B -irradiation to HDFs impairs the autophagy response in a time and intensity independent manner. However, improving autophagy levels in HDFs with pharmacological activators regulates the UV-B induced cellular stress by decreasing the induction of DNA photo adducts, promoting the DNA repair process, alleviating oxidative and ER stress responses and regulating the expression levels of key cell cycle regulatory proteins. Autophagy also prevents HDFs from UV-B -induced nuclear damage as is evident in Tunnel assay and Acridine Orange/Ethidium Bromide co-staining. Salubrinal, (an eIF2α phosphatase inhibitor) and relieves ER stress response in cells also significantly alleviates the DNA damage and promotes the repair process in UV-B exposed HDFs. P62 silenced HDFs show enhanced DNA damage response and also disturb the tumor suppressor PTEN/pAKT signalling axis in UV-B exposed HDFs whereas Atg7 silenced HDFs reveal an unexpected consequence by decreasing the UV-B -induced DNA damage. Taken together, these results suggest that interventional autophagy offers significant protection against UV-B radiation-induced photo-damage and holds great promise in devising it as a suitable therapeutic strategy against skin pathological disorders.